LAW OF RESEARCH DEVELOPMENT AND UTILIZATION OF FOOD RESOURCES IN THE FRAMEWORK OF STRENGTHENING FOOD SECURITY - Mangesti, Yovita Arie (Jurnal Hukum Magnum Opus, 2020)
AbstractFood security is a multidimensional problem that covers economic, social and legal aspects. This economic problem arises from the existence of commodity aspects in food resources that correlate with the social conditions of the community related to research and use of food, also to the law which becomes the guiding rule in its function to protect the constitutional rights of research and use of food. In this paper, the research covers food availability and affordability, while utilization covers production to food consumption. Availability and affordability of food needs have been done through food diversification, among others by genetic engineering, which then at the utilization level will result in acceleration of the food security program. The interdisciplinary approach results a humanist legal concept of research and utilization by not leaving human aspects and the survival of biological resources, so that in the research and utilization of food resources the existence of life values cannot be reduced by commodity factors. The strengthening of research regulations and the utilization of food resources is carried out by constructing legislation at the level of applicable Government Regulations with the revitalization of the Food Security Institution at the regional level that performs the function of controlling and evaluating research and food resources in the regions within the frame of humanity and justice.Keywords: endurance; food; natural resourcesAbstrakKetahanan pangan adalah masalah multidimensi yang mencakup aspek ekonomi, sosial dan hukum. Masalah ekonomi ini muncul dari adanya aspek komoditas dalam sumber daya pangan yang berkorelasi dengan kondisi sosial masyarakat terkait dengan penelitian dan penggunaan pangan, juga hukum yang menjadi pedoman aturan dalam fungsinya untuk melindungi hak-hak konstitusional penelitian dan menggunakan makanan. Dalam makalah ini, penelitian mencakup ketersediaan dan keterjangkauan pangan, sedangkan pemanfaatan mencakup produksi untuk konsumsi makanan. Ketersediaan dan keterjangkauan kebutuhan pangan telah dilakukan melalui diversifikasi pangan, antara lain oleh rekayasa genetika, yang kemudian pada tingkat pemanfaatan akan menghasilkan percepatan program ketahanan pangan. Pendekatan interdisipliner menghasilkan konsep hukum humanis penelitian dan pemanfaatan dengan tidak meninggalkan aspek manusia dan kelangsungan hidup sumber daya hayati, sehingga dalam penelitian dan pemanfaatan sumber daya makanan keberadaan nilai-nilai kehidupan tidak dapat dikurangi oleh faktor-faktor komoditas. Penguatan peraturan penelitian dan pemanfaatan sumber daya makanan dilakukan dengan membangun undang-undang di tingkat Peraturan Pemerintah yang berlaku dengan revitalisasi Lembaga Ketahanan Pangan di tingkat daerah yang melakukan fungsi mengendalikan dan mengevaluasi penelitian dan sumber daya makanan di wilayah dalam bingkai kemanusiaan dan keadilan.Kata kunci: ketahanan; pangan; sumber daya alam